Femisida di Indonesia: Analisis Naratif Berita Kasus Mutilasi di Surabaya Pada Portal Kompas.id - Nurjanah, Miftahul; Akbar, M. Fikri; Allifiansyah, Sandy (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
This study analyzes the coverage of a mutilation case in Surabaya that befell a woman as part of the phenomenon of femicide in Indonesia. Using a narrative analysis approach, this study examines how Kompas.id constructs narratives, representations of victims and perpetrators, and the framing patterns used. The results show that the media emphasizes sensational aspects and details of violence rather than structural explanations of the roots of gender-based violence. Victims are often reduced to mere objects of news coverage, while perpetrators are described through psychological narratives that obscure the patriarchal dimension of femicide. These findings indicate the persistence of patriarchal discourse in mainstream media in Indonesia. This research contributes to feminist media studies by emphasizing the framing of femicide as a structural issue closely related to gender inequality, rather than merely individual criminal cases.